Shackled: Female Convicts at Moreton Bay, 1826–1839. (March 2017) - Piper, Alana
Abstract : Shackled: Female Convicts at Moreton Bay, 1826–1839. By Jennifer Harrison (Collins Street East, Anchor Books Australia, 2016), pp.x + 271. Twenty‐three Illustrations. Three Tables. AU34.95 (pb).